Hobo mom - Forsman, Charles; Radiguès, Max de, 1982- (Fantagraphics Books, Inc., 2019)
A single father and pre-teen daughter are reunited with the woman who once left them, forcing all three to confront their own notions of happiness and whether someone who covets independence so strongly can ever settle down, no matter the cost.-- <U+01C2>c Provided by publisher.